PENGARUH MARKETING MIX TERHADAP KEPUTUSAN PEMBELIAN KURMA GOLDEN ORIENT (STUDI KASUS TOKO OLEH-OLEH ALKATHIRI SURAKARTA) - Dewani, Mayang Risti; Riptanti, Erlyna Wida; Setyowati, Setyowati (Universitas Veteran Bangun Nusantara, 2023)
Dates originating from Egypt are the best-selling dates in Indonesia. Dates from Egypt have the designation Golden Orient which is produced by the Orient Group. The shape of the large dates, with a soft texture, and cheap, makes the Golden Orient dates in great demand by consumers. This study aims to determine the effect of marketing mix 4P simultaneously and partially on purchasing decisions of Golden Orient Dates. This research is also to find out the most influential variables on consumer decisions to buy Golden Orient Dates. Determining the location purposively with 100 respondents. The type of data used is Likert scale primary data, answers obtained through questionnaires and interviews. Data analysis used multiple linear regression with SPSS 25. The results of the analysis explained simultaneously eight variables influencing purchasing decisions. Individually, variables of quality, packaging, price affordability, and price suitability influencing purchasing decisions. Golden Orient dates have good quality in terms of texture and taste, and have attractive packaging. The price of Golden Orient dates is affordable with quality according to the price. Accessibility, parking facilities, advertising, and advertising time have no significant effect. Companies need evaluation related to this matter to improve purchasing decisions. The most dominant variable influencing is price affordability, because it is cheaper than other stores.